2014
DOI: 10.4103/0972-2327.128555
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility weighted magnetic resonance imaging of brain: A multifaceted powerful sequence that adds to understanding of acute stroke

Abstract: Context:To evaluate the additional information that susceptibility weighted sequences and datasets would provide in acute stroke.Aims:The aim of this study were to assess the value addition of susceptibility weighted magnetic resonance imaging (SWI) of brain in patients with acute arterial infarct.Materials and Methods:All patients referred for a complete brain magnetic resonance imaging (MRI) between March 2010 and March 2011 at our institution had SWI as part of routine MRI (T1, T2, and diffusion imaging). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
3
1
Order By: Relevance
“…In contrary to our research, the research of Naik et al [22] found that of the 22 cases investigated with hemorrhage, 17 had petechial hemorrhage and 5 cases had macro-hemorrhage within the infarct bleeds. Also, they reported that SWI can provide vital information on haemorrhage and vascular thrombosis, which could be useful in determining the severity of an acute stroke.…”
Section: A B Dcontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrary to our research, the research of Naik et al [22] found that of the 22 cases investigated with hemorrhage, 17 had petechial hemorrhage and 5 cases had macro-hemorrhage within the infarct bleeds. Also, they reported that SWI can provide vital information on haemorrhage and vascular thrombosis, which could be useful in determining the severity of an acute stroke.…”
Section: A B Dcontrasting
confidence: 99%
“…On the other hand, Darwish et al [21] found that 11 cases (55%) and 9 cases (45%) have infarctions of the right and left MCA territories respectively. Our research agreed with Naik et al [22] showed that the infarcts with hemorrhage are distributed as follows: 11-middle cerebral artery, 1-anterior cerebral artery, 5-posterior cerebral artery, 1anterior inferior cerebellar artery, 3-superior cerebellar artery, and 1-posterior inferior cerebellar artery.…”
Section: A B Dsupporting
confidence: 93%
“…Susceptibility-weighted sequences such as T2 * GRE and SWI are central to the MRI-based acute stroke workup ( 31 , 32 ). SWI sequences provide reliable information on a potential hemorrhagic transformation but may also outline the occluded vessel depending on clot composition ( 9 , 13 , 15 , 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…is a useful technique in detecting micro-bleeds (Liu et al, 2017;Naik, Viswamitra, Kumar, & Srinath, 2014;Ryan et al, 2015) and diffuse neuropathology detected with SWI has been related to ToM deficits in paediatric TBI patients (Ryan et al, 2015). Unfortunately, DTI and SWI sequences were not part of the imaging protocol during the time of our study.…”
Section: Discussionmentioning
confidence: 99%